(untitled) (Development Engineering Conferences Center Articles Database, 2025)
The aim of this study was to investigate the comparative effect of these drugs, Capecitabine and Gemcitabine, on their protein Alpha-fetoprotein (AFP) in Liver cancer. This was done by the method of Docking molecular, which was done using Pyrex and Chimera software. The positions of these drugs on the target protein were examined, and according to the RMSD and Binding affinity obtained from the placement of these drugs on AFP, it was concluded of Capecitabine that the binding affinity was more negative (-6.9) and the RMSD higher,(RMSD Lower case :21.327),(RMSD Upper case :22.401) has a better and greater effect on Alpha-feto protein .